More women on supervisory boards: Increasing indications that the effect of the gender quota extends to executive boards - Anja Kirsch; Katharina Wrohlich (DIW Weekly Report, 2020)
The statutory gender quota for supervisory boards is effective: the proportion of women on supervisory boards has increased over the past years, especially in the companies subject to the quota. But is the quota creating trickle-down effects for executive boards? As the second part of the DIW Berlin Women Executives Barometer, this report analyzes whether a relationship between the growth of the proportion of women on supervisory boards and on executive boards exists. The key result is that a relationship is discernible and there are good indications that the gender quota for supervisory boards positively influences the presence of women on executive boards. However, a cause and effect relationship has yet to be demonstrated. Answers from interviews with 60 supervisory board members of both genders show they have a wide range of opportunities to influence how executive board positions are filled and thus to work towards more women in upper management. In many places, however, these possibilities have not yet been fully exhausted. Further political and social pressure and new forms of work organization could help to increase the proportion of women in management positions in a sustainable way.
Keywords: D22; J16; J59; J78; L21; L32; M14; M51; 330; corporate boards; board composition; boards of directors; board diversity; Europe; women directors; gender equality; gender quota; Germany; management; private companies; public companies; supervisory boards; executive boards; CEOs; women